2015
DOI: 10.1111/jopr.12277
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient and Cost‐Effective Technique to Construct an Intraoral Central Bearing Tracing Device

Abstract: Intraoral central bearing tracing has been shown to be a predictable way of recording and verifying centric relation position for patients. Existing tracing devices are challenging to use due to several significant clinical limitations. In comparison to commercially available counterparts, this article presents a technique that simplifies instrumentation and clinical steps to make an intraoral tracer for making centric relation records, determining occlusal vertical dimension, and detecting deflective occlusal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
2
0
1
Order By: Relevance
“…The authors claim that their technique is simple, is easy to master, and requires less armamentarium. Lin and Wagner[ 31 ] described an efficient and a feasible technique to construct an intraoral central bearing tracing device which can be used to make CR records, to determine vertical dimension of occlusion, and to detect occlusal interferences. Čimić et al [ 32 ] compared the reproducibility of CR records fabricated with chin point guidance with jig in patients with disc displacement with reduction and healthy individuals and found that there was no difference in the reproducibility of CR records.…”
Section: Discussionmentioning
confidence: 99%
“…The authors claim that their technique is simple, is easy to master, and requires less armamentarium. Lin and Wagner[ 31 ] described an efficient and a feasible technique to construct an intraoral central bearing tracing device which can be used to make CR records, to determine vertical dimension of occlusion, and to detect occlusal interferences. Čimić et al [ 32 ] compared the reproducibility of CR records fabricated with chin point guidance with jig in patients with disc displacement with reduction and healthy individuals and found that there was no difference in the reproducibility of CR records.…”
Section: Discussionmentioning
confidence: 99%
“…The well‐fitting monolithic denture is an ideal platform for using a mandibular tracing device to refine the occlusion and determine centric relation (Fig 6). 28 Unlike traditional trial bases that need to be modified to prevent damage to the stone cast, the digital printed base fits as accurately as the definitive prosthesis which makes the tracing process easier for the clinician. This also makes evaluation of phonetics much easier to accomplish.…”
Section: Clinical Workflowsmentioning
confidence: 99%
“…Sin duda alguna, el registro de la dimensión vertical en el paciente totalmente desdentado ha sido por años un tema controvertido, y es uno de los puntos pendientes de la prostodoncia. 2,3 Estamos de acuerdo en que la dimensión vertical está determinada por la longitud óptima de contracción de los músculos elevadores, fijando de esa manera una distancia intermaxilar constante dentro de la cual hacen erupción las piezas dentarias, lográndose así la dimensión vertical oclusiva. 4 , 5 También estamos de acuerdo, que es de suma importancia en el desdentado total registrar correctamente dicha dimensión vertical oclusiva para poder devolver mediante las prótesis las estructuras perdidas, en armonía con las ATM, el sistema neuromuscular y la estética.…”
Section: Introduccionunclassified